Uterus Transplants and the Potential for Harm: Lessons From Commercial Surrogacy. Issue 3 (6th July 2020) - Barn, Gulzaar
Abstract: The human uterine transplant (UTx) is being developed as a procedure to alleviate absolute uterine factor infertility (AUFI). In light of recent UTx advances in India, I suggest that key ethical concerns would emerge if this procedure were to become established as part of India's liberalised assisted reproduction industry. On evidence‐based projections, UTx would be likely to harm vulnerable populations in two key ways. Firstly, I suggest that a commercial model for uteri procurement is primed to develop due to various structural factors that facilitated the boom in commercial surrogacy remaining in place, despite commercial surrogacy having been outlawed. I outline ways in which Indian commercial surrogacy arrangements exhibited exploitation and suggest that a commercial UTx model would be similarly exploitative, with many background features of exploitative surrogacy remaining constant. The second way in which the development of UTx in India might pose harm is through the difficulty in obtaining proper informed consent, even under altruistic arrangements. I argue that structural factors, including a cultural deference to doctors, lack of medical understanding displayed by vulnerable populations, and a privatised healthcare system with little regulatory oversight, would render it difficult to obtain proper informed consent from living donors. Further, factors peculiar to UTx, such as its experimental nature, and the unknown and novel risks and harms it poses, heighten this difficulty. Accordingly, UTx in India would be unlikely to meet the Montreal criteria for the ethical feasibility of uterine transplantation and should thus raise ethical alarm.